DEVELOPING THE PROFESSIONAL COMPETENCE OF FUTURE ENGINEERS USING MODERN SCIENTIFIC ACHIEVEMENTS IN PHYSICS TRAINING - Erkin Khalimov (European Science Publishing, 2024)
The article reflects on the study of concepts and laws such as the structure, mechanical properties of nanomaterials in Physical Science in order to increase professional training in engineering specialties by linking them to science.
Keywords: Physics, nanotechnology, nanomaterials, mechanical properties, nanohard, Hall-Petch's law, Oliver and Farr's method, indenter, robustness, hardness, integration.